10-Day Versus 14-Day Quadruple Concomitant Nonbismuth Therapy for the Treatment of Helicobacter pylori Infection: Results From a Randomized Prospective Study in a High Clarithromycin Resistance Country. Issue 6 (July 2020) - Apostolopoulos, Periklis; Ekmektzoglou, Konstantinos; Georgopoulos, Sotirios; Chounta, Eleni; Theofanopoulou, Antonia; Kalantzis, Chrisostomos; Vlachou, Erasmia; Tsibouris, Panagiotis; Alexandrakis, Georgios
Abstract : Goals: The aim of this study was to investigate the implementation of a 14-day quadruple nonbismuth concomitant regimen, as proposed by recent Guidelines and Consensus Statements. Background: In Greece, a region with >20% clarithromycin resistance where bismuth is unavailable, the 10-day quadruple concomitant scheme has already been adopted as the accepted first-line Helicobacter pylori eradication treatment. Study: Our prospective randomized study included 364 patients with newly diagnosed H. pylori infection, randomized to receive a 10-day or a 14-day nonbismuth quadruple concomitant scheme. Treatment outcome was assessed by C 13 -urea breath test and/or histology at least 4 weeks after therapy. Intention to treat and per protocol analyses of the eradication rates were performed. Secondary endpoints included patient adherence, safety, and the impact of prior antibiotic exposure in treatment efficacy. Results: The overall eradication rates of the 2 treatments were 87.9% versus 87.4% in the intention to treat analysis, P =1.000, and 93% versus 94.1%, P =0.859, in the per protocol analysis for the 10-day and the 14-day treatment group, respectively. Both groups displayed excellent compliance rates (99.5% for the 10-day vs. 96.2% for the 14-day treatment duration, P =0.067). As regards treatment safety, serious adverse events that led to the discontinuation of both regimens were few, with no statistical difference between the 2 groups (0.5% in the 10-day group and 2.2% in the 14-day group, P >0.05). Previous antibiotic exposure was not significant with regard to treatment efficacy. Conclusion: In Greece, the 10-day concomitant nonbismuth quadruple regimen for first-line treatment remains the most efficient strategy for H. pylori eradication.